2019
DOI: 10.1016/j.bja.2019.04.055
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence of and risk factors for venous thrombosis in children with percutaneous non-tunnelled central venous catheters

Abstract: Background: Venous thrombosis (VT) in children is often associated with a central venous catheter (CVC). We aimed to determine the incidence of VT associated with percutaneous non-tunnelled CVCs in a general paediatric population, and to identify risk factors for VT in this cohort. Methods: Observational, prospective study enrolling consecutive patients at a tertiary multidisciplinary paediatric hospital. A total of 211 percutaneous, non-tunnelled CVCs were analysed. Data regarding potential risk factors for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 21 publications
2
35
1
Order By: Relevance
“…44 Risk factors for CVC-related DVT include the duration of catheterization, catheter type (peripherally inserted central catheters [PICC] may have greater risk than CVC), number of lumens, insertion site, and catheter-to-vein diameter ratios. 8,[44][45][46][47][48][49] In a multicenter, prospective observational cohort study, Jaffray et al reported a cumulative incidence of CVC-related DVT of 5.9 AE 0.63%; among these, 80% were noted in PICC lines. 49 While a smaller-caliber PICC line may limit obstruction of venous blood flow when compared with a larger-bore CVC in any particular vein, newly placed PICC lines in children presenting with critical illness at times remain in situ for extensive durations compared with larger-bore CVCs in an effort to facilitate hospital or PICU discharge.…”
Section: Central Venous Catheterizationmentioning
confidence: 99%
“…44 Risk factors for CVC-related DVT include the duration of catheterization, catheter type (peripherally inserted central catheters [PICC] may have greater risk than CVC), number of lumens, insertion site, and catheter-to-vein diameter ratios. 8,[44][45][46][47][48][49] In a multicenter, prospective observational cohort study, Jaffray et al reported a cumulative incidence of CVC-related DVT of 5.9 AE 0.63%; among these, 80% were noted in PICC lines. 49 While a smaller-caliber PICC line may limit obstruction of venous blood flow when compared with a larger-bore CVC in any particular vein, newly placed PICC lines in children presenting with critical illness at times remain in situ for extensive durations compared with larger-bore CVCs in an effort to facilitate hospital or PICU discharge.…”
Section: Central Venous Catheterizationmentioning
confidence: 99%
“…Hence, CRT is an urgent concern because it may promote chronic venous occlusion resulting in loss of vascular access. This condition may increases morbidity, mortality, length of hospital stay, and cost of healthcare [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings, the prevalence of thrombosis was 18.3% (95%CI: 11.2%-28.6%), and the prevalence of catheter malfunction was 16.1% (95%CI: 9.2%-26.7%). Östlund et al showed that the incidence rate for CVC-related Venous Thrombosis (VT) was 29.6 per 1000 [38]. Also, in the study of Hughes et al on hemodialysis patients in Nigeria, the dislodging rate was 6 (5.5%), and the low flow rate was 9 (8.3%) [39].…”
Section: Discussionmentioning
confidence: 99%